Pelatihan Tentang Menggunakan Media Sosial Untuk Pemasaran Pada Pengelola Jasa Hapus Tato (PROCARE) Di Kota Klaten. - Erma Widyastuti (Universitas Muhammadiyah Klaten, 2023)
The aim of the service is to provide knowledge related to using social media for marketing to managers of tattoo removal services (procare) in the city of Klaten. Social media, in a marketing context, refers to online interactive platforms that facilitate interaction, content sharing, and collaboration opportunities among individuals, communities, and organizations. This includes various platforms such as Facebook, Instagram, Twitter, LinkedIn, TikTok, YouTube, and many more. As technology and internet accessibility develop, this number is expected to continue to grow, providing endless opportunities for innovative and effective marketing. The essence of a marketing strategy on social media is to achieve concrete business goals. This includes increasing brand awareness, building deeper relationships with customers, increasing sales, gaining and maintaining market share, and measuring campaign performance and effectiveness through relevant metrics. Having a presence on social media can also help respond and manage brand image quickly and effectively when various situations arise. This training is a provision for tattoo removal service managers (procare) regarding the use of social media as a marketing strategy.